The immunosuppressive role of Edn3 overexpression in the melanoma microenvironment. (29th July 2021) - Freitas, Juliano T.; Lopez, Jesus; Llorian, Claudia; Boroni, Mariana; Kos, Lidia
Abstract: Endothelins are cytokines expressed in the microenvironment of several tumors. To identify which stromal cells in the melanoma microenvironment respond to endothelin, we injected murine melanoma cell lines B16F10, YUMM1.7, and YUMMER1.7 in a transgenic mouse that overexpresses endothelin 3 (Edn3) under the control of the keratin 5 promoter in the skin ( K5‐Edn3 ). All cell lines developed larger tumors in K5‐Edn3 mice than in control animals. In YUMM1.7 tumors, the Edn3 receptor, endothelin receptor B (Ednrb), was expressed in several stromal cell types including immune cells. This result was validated by the identification of Ednrb‐positive stromal cells in human melanoma from previously published RNA‐seq data. Regulatory T cells (Tregs) and dendritic cell numbers were significantly higher in K5‐Edn3 tumors when compared to control tumors. Edn3 increased Treg proliferation in vitro and the expression of FOXP3. YUMM1.7‐GFP tumors in K5‐Edn3 mice were sensitive to immune checkpoint inhibitor (anti‐CTLA‐4) as well as to Ednrb blockage (BQ‐788). Our results indicate that Ednrb signaling has an important role in the melanoma microenvironment where it mediates immunosuppression resulting in escape from tumor immunity.